Dynamic Tests on a Series Wound DC Motor. Simulation of the Braking of the Vehicle Driven by the Motor - Szántó, Attila; Szíki, Gusztáv Áron; Sarvajcz, Kornél (International Journal of Engineering and Management Sciences, 2019)
In the following we present the role and contribution of vehicle dynamics simulation to vehicle development in the University of Debrecen Faculty of Engineering. We present the input technical parameters which are necessary for the simulation of the series wound DC motor – which drives the vehicle – and also the procedure for their measurement together with the results of dynamic test measurements on the motor. The latest version of our vehicle dynamics simulation program –which is capable of the simulation of braking too – is also presented here.